Enhanced policy adequacy facilitates national climate adaptation tracking across Africa - Nowak, Andreea C.; Njuguna, Lucy; Ramirez Villegas, Julian; Reidsma, Pytrik; Crumpler, Krystal; Rosenstock, Todd S (Nature Portfolio, 2024)
Inadequate information in national adaptation policies limits the ability to track national adaptation progress in Africa. Enhancing coverage, consistency and robustness of these policies offers a clear path to establish effective, nationally led adaptation-tracking infrastructure.